2014
DOI: 10.1111/1471-0528.13201
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal vitamin C and E supplementation in smokers is associated with reduced placental abruption and preterm birth: a secondary analysis

Abstract: OBJECTIVE Smoking and Preeclampsia (PE) are associated with increases in preterm birth, placental abruption and low birth weight. We evaluated the relationship between prenatal vitamin C/E supplementation and perinatal outcomes by maternal self-reported smoking status focusing on outcomes known to be impacted by maternal smoking. DESIGN/POPULATION A secondary analysis of a multi-center trial of vitamin C/E supplementation starting at 9–16 weeks in low-risk nulliparous women with singleton gestations. METHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 39 publications
1
25
0
3
Order By: Relevance
“…We propose the differences are explained by the antioxidant effects of omega-3 supplementation combating the oxidative stress caused by cigarette toxins. This is further supported by the similar findings of Abramovici et al 31 who showed supplementation with vitamins C and E, which are antioxidants, reduced the risk of preterm birth in smokers but not nonsmokers. Since smokers have lower serum levels of omega-3 fatty acids and vitamins C and E, 19, 32 this may explain why supplementation has a preferential effect in smokers compared to nonsmokers.…”
Section: Commentsupporting
confidence: 80%
“…We propose the differences are explained by the antioxidant effects of omega-3 supplementation combating the oxidative stress caused by cigarette toxins. This is further supported by the similar findings of Abramovici et al 31 who showed supplementation with vitamins C and E, which are antioxidants, reduced the risk of preterm birth in smokers but not nonsmokers. Since smokers have lower serum levels of omega-3 fatty acids and vitamins C and E, 19, 32 this may explain why supplementation has a preferential effect in smokers compared to nonsmokers.…”
Section: Commentsupporting
confidence: 80%
“…The effect of maternal smoking on newborn lung function was also associated with the maternal genotype for the α5 nAChR receptor gene (rs16969968) (p<0.001 for interaction), which is the α5 nAChR structural polymorphism that has the strongest link to lung disease (55) (Figure 3). This study was not powered to examine preterm births between the randomized groups, but a large trial (56) of vitamin C (1000 mg) and vitamin E (400 IU) supplementation during pregnancy found a reduction in preterm birth (RR 0.76; 95% CI 0.58-0.99) and placental abruption in the treated versus untreated smokers.…”
Section: Potential Approaches For Primary Preventionmentioning
confidence: 99%
“…42 Vitamin C/E supplementation also reduced placental abruption and preterm birth in women who smoked. 43 Similarly, administration of polyphenols found in pomegranate juice 44 has been shown to reduce placental oxidative stress while the carot- linked to reduced SOD activity in the placenta, one report has found that plasma levels of SOD1 and SOD3 are increased in this disease. 46 Superoxide dismutase activity has also been shown to be reduced in placentas of preterm and IUGR babies with corresponding reductions in both copper and zinc reported.…”
Section: Oxidative Stressmentioning
confidence: 98%
“…111 Additional benefits in smokers. 43 Active transport across the placenta most likely by SVCT2 (Sodium-dependent vitamin C transporter 2) but also by glucose transporters. 112 When in combination with Vitamin E, reduced placental oxidative stress in isolated placentas 42 Vitamin D Hypothesized to improve brain structure and function.…”
Section: Mgmentioning
confidence: 99%